Possibility of using modified fly ash and organic fertilizers for remediation of heavy-metal-contaminated soils. (15th February 2021) - Hu, Xiongfei; Huang, Xunrong; Zhao, Hanghang; Liu, Fuhao; Wang, Lu; Zhao, Xin; Gao, Pengcheng; Li, Xiuying; Ji, Puhui
Abstract: New modified fly ash is an excellent amendment for stabilising soil heavy metals. In this study, new modified fly ash and an organic fertilizer were employed for soil heavy metal remediation. The applications of the organic fertilizer to the soil can lead to buffering of the alkalinity of new modified fly ash. The results of mixture treatments were better than those of the application of only new modified fly ash for free heavy metal reduction. Among them, the treatment of 0.4% organic fertilizer and 4% new modified fly ash led to a reduction in the Mehlich-3 extractable cadmium (Cd), copper (Cu), and lead (Pb) of 49.0%, 53.5%, 67.83%, respectively, but the treatment of 4% new modified fly ash led to the reduction of 47.6%, 48.09%, and 62.73%, respectively. By the end of the experiment, the urease and alkaline phosphatase activities in the soil had considerably improved, and those activities in the soil treated with 0.4% organic fertilizer and 4% new modified fly ash increased by 2.21 and 3.2 times, respectively, compared with that in the control treatment soil. Similarly, organic matter and available N, P, and K considerably improved with the addition of the organic fertilizer. This study demonstrated the importance of the application of organic fertilizers and new modified fly ash mixture for the remediation of HM-contaminated soils and the improvement of soil quality. Graphical abstract: Image 1